2013
DOI: 10.1007/s00259-013-2379-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic imaging of prostate cancer with magnetic resonance spectroscopy and mass spectrometry

Abstract: Metabolomic imaging of prostate cancer (PCa) aims to improve in vivo imaging capability so that PCa tumors can be localized non-invasively to guide biopsy and evaluated for aggressiveness prior to prostatectomy, as well as to assess and monitor PCa growth for newly biopsy-diagnosed, asymptomatic PCa patients. Metabolomics studies global variations of metabolites with which malignancy conditions can be evaluated by profiling the entire measurable metabolome, instead of focusing only on certain metabolites or is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…While PET imaging with radiotracers targeting alterations of particular biochemical pathways have proven to be successful in many cancers, metabolic profiles may have even greater potential for diagnosis and disease monitoring. In this issue, Spur et al review methods and results based on MRS and mass spectrometry (MS) in prostate cancer [17]. While MS requires sampling of tissue (or body fluids), it can assay large numbers of metabolites at low concentrations.…”
Section: Mri and Pet/mrmentioning
confidence: 99%
“…While PET imaging with radiotracers targeting alterations of particular biochemical pathways have proven to be successful in many cancers, metabolic profiles may have even greater potential for diagnosis and disease monitoring. In this issue, Spur et al review methods and results based on MRS and mass spectrometry (MS) in prostate cancer [17]. While MS requires sampling of tissue (or body fluids), it can assay large numbers of metabolites at low concentrations.…”
Section: Mri and Pet/mrmentioning
confidence: 99%
“…Either NMR-or MS-based, the metabolomics approach has found a wide scope of applications in disease research and, in particular, in cancer research, since altered metabolism is a recognized important cancer hallmark [18,19], with cancer cells exhibiting a distinct metabolic behavior to normal cells and impacting on systemic metabolism. The significant increase in the number of reports on cancer metabolomics, in recent years, is illustrated by many recent reviews, either generally addressing cancer research [20][21][22][23][24][25][26][27] or dedicated to a specific cancer type (Table 1) [12,[28][29][30][31][32][33][34][35][36][37][38][39][40]. This reflects the recognized importance of assessing metabolic changes related to tumor onset and progression as part of a novel biomarkers discovery avenue toward improved methodologies for cancer detection and monitoring.…”
mentioning
confidence: 96%
“…Furthermore, compared to mass spectrometry (MS), MRS has the significant advantage of a possible in vivo translation, as the histological structure of tissue samples is not altered during analysis 61 .…”
Section: Challenges In Prostate Cancer Diagnosticsmentioning
confidence: 99%
“…After the first successful application of the MRSI technique within brain tumor research, the method was implemented to PCa studies 61,85 . It has been shown that the combination of MRS and MRI significantly improved the cancer detection rate compared to each method alone 86 .…”
Section: Challenges In Prostate Cancer Diagnosticsmentioning
confidence: 99%